2023
DOI: 10.1057/s41599-023-02228-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the employment motivation, job satisfaction and dissatisfaction of university English instructors in public institutions: a Chinese case study analysis

Gareth Morris,
Junhua Mo

Abstract: This study considers the important areas of language teacher employment motivation, job satisfaction and dissatisfaction in state universities in China. This is an area in which there is a distinct lack of research studies. Through an exploratory case study analysis, and depth enlightening interviews, this paper considers the experiences of two outwardly successful doctorate status educators, examining their early career motives and subsequent employment satisfaction and dissatisfaction. It finds that these En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Furthermore, in a study conducted by Morris and Mo (2023), it was found that English teachers in China participating in their research are largely satisfied with their work, but they also expressed dissatisfaction in certain areas. For example, they appreciated the teaching load and respect given to university professors, but had concerns about their long-term professional development.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in a study conducted by Morris and Mo (2023), it was found that English teachers in China participating in their research are largely satisfied with their work, but they also expressed dissatisfaction in certain areas. For example, they appreciated the teaching load and respect given to university professors, but had concerns about their long-term professional development.…”
Section: Resultsmentioning
confidence: 99%